Home in the Poetry of Saudi Arabia Poets: Taher Zamakhshari an Example of a Distinguished Arab - Dahami, Yahya Saleh Hasan (Universitas Islam Negeri Sumatera Utara Medan, 2024)
Poets frequently extol and admire their own lands. Home is a very important topic for Saudi poets, Arab poets, and, I would venture to say, for every intellectual person. The same topic was directed by a number of Saudi poets, who provided us with beautiful lyrical poetry works honoring the Kingdom of Saudi Arabia, their country of origin. The study uses Taher Zamakhshari's poem